Size of fat body trophocytes and the ovarian development in workers and queens of Melipona quadrifasciata anthidioides - Paes de Oliveira, V. T.; Cruz-Landim, C. [UNESP] (My University, 2003)
The correlation between trophocyte size and ovarian development is negative in workers and positive in queens of Melipona quadrifasciata anthidioides. The nurse workers which have the ovaries in a higher developmental stage, present smaller fat body cells them newly-emerged ones. In newly-emerged and nurse workers the trophocytes seem to be delivering their stored products, among which probably vitellogenin. As in workers the cell size variations do not support the occurrence of proteic synthesis or the increasing in reverses storage after the adult emergence, the products released from the trophocytes must come from cellular reserves remaining from the larval phase. This datum is in agreement with the early and brief vitellogenic phase in the ovaries of this caste. In foragers the trophocyte size seen stabilized. In queens it was verified considerable increasing in the trophocyte size from virgin to physogastric queen, as well as the maintenance of the size during all fertile life of the queen.
Keywords: Invertebrata; Melipona quadrifasciata